Evaluating the impact of neurosurgical rotation experience in Africa on the interest and perception of medical students towards a career in neurosurgery: a protocol for a continental, cross-sectional study. Issue 2 (2nd April 2022) - Ooi, Setthasorn Zhi Yang; Dada, Olaoluwa Ezekiel; Bukenya, George William; Kenfack, Yves Jordan; Le, Chi; Ohonba, Efosa; Adeyemo, Emmanuel; Narain, Kapil; Awad, Ahmed Khaled; Barrie, Umaru; Sichimba, Dawin; Ogunfolaji, Oloruntoba; et al.
Abstract: Introduction: Africa has the second highest neurosurgical workforce deficit globally. Despite the many recent advancements in increasing neurosurgical access in Africa, published reports have shown that the vast majority of undergraduate students have little or no exposure to neurosurgery. The lack of exposure may pose a challenge in reducing the neurosurgical workforce deficit, which is one of the long-term strategies of tackling the unmet burden of disease. Students may also miss the opportunity to appreciate the specialty and its demands as well as nurture their interest in the field. This study aims to assess the impact of a neurosurgical rotation during medical school in shaping the perception and interest of students towards a career in neurosurgery. Methods: The cross-sectional study will be conducted through the dissemination of a self-administered e-survey hosted on Google Forms from 21st February 2021 to 20th March 2021. The survey will contain five-point Likert scale, multiple-choice and free-text questions. The structured questionnaire will have four sections with 27 items: (i) socio-demographic background, (ii) neurosurgical experience, (iii) perception towards a neurosurgical career and (iv) interest in a neurosurgical career. All consenting medical students in African medical schools who are in their clinical years (defined as fourth to sixth years or higher years of study) will be eligible. Odds ratios and their 95% confidence intervals, Wilcoxon rank-sum test, Welch t -test and adjusted logistic regression models will be used to test for associations between independent and dependent variables. Statistical significance will be accepted at P  < 0.05.